Plan de publicidad y promoción para incrementar las ventas en el Almacén Autorepuestos Jhonson del cantón Buena Fe provincia de los Ríos, periodo 2015 - Navarrete Peña, Isabel Carolina (2015)
The research working "Plan advertising of advertising and Promotion to increase sales in the Jhonson Store Johnson in Buena Fe city, Los Rios, province period 2015" it has as main objective to keep and attract new customers through strategies to stay on the market, that is why it is important that people know where to purchase their parts; and therefore it is necessary that the store made itself known advertising and promotion for the acquisition and retention of customers. Basic to the realization of this research characteristics types, methods, techniques related to the project supported with field research and literature that allowed the research work feasible for implementation were used. In the field research made 14 questions to customers and 10 to potencial customers, whose results were great help and we can use the base for decision making in the elaboration of the PLAN ADVERTISING AND PROMOTION. It is conclude that Jhonson Store customer acceptance but has not reached the goal it has set; therefore the design of advertising and promotion plan being proposed will allow the store to obtain an increase in the customer base, sales; hence their profitability and allow owners to take all necessary steps to make it possible to achieve the objectives and raised in this research work measures.